2013
DOI: 10.1590/s0102-09352013000600023
|View full text |Cite
|
Sign up to set email alerts
|

Serum bactericidal activity as indicator of innate immunity in pacu Piaractus mesopotamicus (Holmberg, 1887)

Abstract: The immune system of teleost fish has mechanisms responsible for the defense against bacteria through protective proteins in several tissues. The protein action can be evaluated by serum bactericidal activity and this is an important tool to analyze the immune system. Pacu, Piaractus mesopotamicus, is one of the most important fish in national aquaculture. However there is a lack of studies on its immune responses. In order to standardize and assess the accuracy of the serum bactericidal activity assay, fish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…The fish immune system has mechanisms responsible for protection against bacteria through protective protein formation in numerous tissues. Such proteins can be assessed by serum bactericidal activity which is an essential tool to analyse the immune system (Biller‐Takahashi, Takahashi, Pilarski, Sebastião, & Urbinati, ). The concentration of these protective proteins was increased as a result of bacterial infection, leading to a decrease in colony‐forming unit values which expressed as well as an enhanced serum bactericidal activity (Biller‐Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The fish immune system has mechanisms responsible for protection against bacteria through protective protein formation in numerous tissues. Such proteins can be assessed by serum bactericidal activity which is an essential tool to analyse the immune system (Biller‐Takahashi, Takahashi, Pilarski, Sebastião, & Urbinati, ). The concentration of these protective proteins was increased as a result of bacterial infection, leading to a decrease in colony‐forming unit values which expressed as well as an enhanced serum bactericidal activity (Biller‐Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of synbiotics in terms of protection against threatening pathogens can be validated either in vitro or in vivo by challenge tests (Cerezuela et al, ). The presence of protective components in fish blood can be estimated by assessing plasma bactericidal activity, and such assessment is a reliable tool to analyse the fish innate response (Biller‐Takahashi, Takahashi, Pilarski, Sebastião, & Urbinati, ). This study demonstrated that short‐term supplementation with Lacto Forte at a low dose had no pronounced effect on plasma bactericidal capacity, while long‐term supplementation could fortify plasma bactericidal activity against A. hydrophila and P. fluorescens .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antimicrobial agents in fish blood can be evaluated by serum bactericidal activity and this is an important tool to analyze the innate immune system (Biller-Takahashi et al 2013). In fact, independently of the effect of molecules and the mechanisms involved in the microbial killing, the measurement of the microbicidal activity is a very realistic approximation (Guardiola Abellán 2014).…”
Section: Discussionmentioning
confidence: 99%